2019
DOI: 10.3390/antiox8090329
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Nelumbo nucifera Leaf Extract on 2-Acetylaminofluorene-induced Hepatocarcinogenesis Through Enhancing Antioxidative Potential and Alleviating Inflammation in Rats

Abstract: Leaf extract of Nelumbo nucifera (NLE) has been demonstrated to possess anti-atherosclerosis, improve alcohol-induced steatohepatitis, prevent high-fat diet-induced obesity, and inhibit the proliferation and metastasis of human breast cancer cells. This study determines the chemopreventive role of NLE against 2-acetylaminofluorene (AAF)-induced hepatocellular carcinoma (HCC) in rats. AAF was used to induce hepatocarcinogenesis in rats through genetic and nongenetic effects. After administration for 12 weeks, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Ten μL liver homogenates were subjected to analyze the SOD, CAT, and GSH-Px activities as in previous reports 17 , 18 . CAT was measured by adding 0.03 M H2O2, and the absorption was detected at 240 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Ten μL liver homogenates were subjected to analyze the SOD, CAT, and GSH-Px activities as in previous reports 17 , 18 . CAT was measured by adding 0.03 M H2O2, and the absorption was detected at 240 nm.…”
Section: Methodsmentioning
confidence: 99%
“…In decade, our laboratory dedicated to the research on the health care of Nelumbo nucifera leaves. We found that GA is the major ingredients of Nelumbo nucifera leave extracts (NLE) via HPLC analysis, and demonstrated that NLE improved hepatic injuries, atherosclerosis, obesity, breast cancer, diabetes, and hepatocarcinogenesis [13,14,15,16,17,18]. In this study, we attempted to confirm the anti-melanogenesis of NLE and GA in B16F1 melanoma cells, and we revealed that NLE exerted a better inhibition of melanogenesis than GA.…”
Section: Introductionmentioning
confidence: 88%
“…Yang et al demonstrated that the leaf extract of Nelumbo nucifera (NLE) possesses anti-atherosclerosis properties. e supplementation of NLE also increases the expression of Nrf2 and its downstream targets [47]. Hence, using NLE to upregulate the function of Nrf2 can be developed into a rational treatment for atherosclerosis.…”
Section: Atherosclerosis (As)mentioning
confidence: 99%
“…Strengthens antioxidative potential and alleviates inflammation [47] Enhances the expression of HO-1 [48] Mediates atherosclerosis by saturated fatty acids [49] Arrhythmia Produces antioxidant enzymes to reverse oxidative damage [52] Activates the NO pathway [53] Hypertensive heart disease…”
Section: Viral Myocarditismentioning
confidence: 99%